ST-Segment Elevation and Fractionated Electrograms in Brugada Syndrome Patients Arise From the Same Structurally Abnormal Subepicardial RVOT Area but Have a Different Mechanism. (December 2015) - ten Sande, Judith N.; Coronel, Ruben; Conrath, Chantal E.; Driessen, Antoine H.G.; de Groot, Joris R.; Tan, Hanno L.; Nademanee, Koonlawee; Wilde, Arthur A.M.; de Bakker, Jacques M.T.; van Dessel, Pascal F.H.M.
Abstract : Background—: Brugada syndrome (BrS) is characterized by a typical ECG pattern. We aimed to determine the pathophysiologic basis of the ST-segment in the BrS-ECG with data from various epicardial and endocardial right ventricular activation mapping procedures in 6 BrS patients and in 5 non-BrS controls. Methods and Results—: In 7 patients (2 BrS and 5 controls) with atrial fibrillation, an epicardial 8×6 electrode grid (interelectrode distance 1 mm) was placed epicardially on the right ventricular outflow tract (RVOT) before video-assisted thoracoscopic surgical pulmonary vein isolation. In 2 other BrS patients, endocardial, epicardial RV (CARTO), and body surface mapping was performed. In 2 additional BrS patients, we performed decremental preexcitation of the RVOT before endocardial RV mapping. During video-assisted thoracoscopic surgical pulmonary vein isolation and CARTO mapping, BrS patients (n=4) showed greater activation delay and more fractionated electrograms in the RVOT region than controls. Ajmaline administration increased the region with fractionated electrograms, as well as ST-segment elevation. Preexcitation of the RVOT (n=2) resulted in ECGs that supported the current-to-load mismatch hypothesis for ST-segment elevation. Body surface mapping showed that the area with ST-segment elevation anatomically correlated with the area of fractionated electrograms and activation delay at the RVOT epicardium. Conclusions—: ST-segment elevation and epicardial fractionation/conduction delay in BrS patients are most likely related to the same structural subepicardial abnormalities, but the mechanism is different. ST-segment elevation may be caused by current-to-load mismatch, whereas fractionated electrograms and conduction delay are expected to be caused by discontinuous conduction in the same area with abnormal myocardium. Abstract : Supplemental Digital Content is available in the text.